Present-day stress-field rotations associated with evaporites in the offshore Nile Delta - Tingay, Mark; Bentham, P.; de Feyter, A.; Kellner, A. (Geological Society of America, 2011)
Evaporitic horizons are routinely interpreted to act as mechanical detachment sequences and thus significantly influence the structural evolution of sedimentary basins and fold-thrust belts. However, over 30 years of global in situ stress analysis have provided only poor evidence to support this widespread assumption. This study examines present-day stress orientations inferred from borehole breakout and drilling-induced fractures in 44 boreholes in the offshore Nile Delta. A total of 446 breakouts and 19 drilling-induced fractures from 37 wells reveal sharply contrasting present-day maximum horizontal stress (SHmax) orientations in sequences above and below the extensive Messinian evaporites of the eastern Nile Delta. A typical deltaic margin-parallel SHmax (E-W in the central and ESE-WNW in the eastern Nile Delta) is observed in parts of the Nile Delta that are below or do not contain evaporites. However, a scattered but largely margin-normal (NNE-SSW) SHmax is observed in sequences underlain by evaporites. The ~90° variation in present-day SHmax orientation above and below the Messinian salts provides the first convincing in situ evidence that evaporite sequences can act as major mechanical detachment horizons. In addition, the margin-normal SHmax orientation is subperpendicular to the strike of nearby active extensional faults, indicating the existence of non-Andersonian faulting in the suprasalt region. Furthermore, the evidence that the Messinian evaporites act as an effective mechanical detachment suggests that suprasalt faulting in the eastern Nile Delta is not the result of basement-related deformation and thus raises doubts about the often postulated extension of the Suez fault zone into the eastern Mediterranean.